The Association between Macronutrient Quality Index and Global Dietary Quality Score with Metabolic Syndrome among Iranian Male Staff Population - Siavash Babajafari; Maryam Taghdir; Hosein Rostami (International Journal of Nutrition Sciences)
Background: Diet quality indices such as Global Dietary Quality Score (GDQS) and Macronutrient Quality Index (MQI) have been suggested to be linked to non-communicable diseases. However, they are rarely studied in relation to metabolic syndrome (MetS). Thus, we aimed to investigate the association between GDQS and MQI with MetS amongIranian male staff.Methods: Four-hundred male personnels aged ≥18 years old were enrolled in this cross-sectional study. The GDQS and MQI were calculated using the measures of a vlidated 168-item food frequency questionaire (FFQ). In addition, by measuring waist circumference (WC), fasting blood sugar (FBS), blood pressure (BP), high density lipoprotein choldesterol (HDL-C), and triglyceride (TG).Results: The prevalence of MetS was 20.3%. In addition, the MQI was inversly and significantly associated with the risk of having high TG in the adjusted model. However, no significant correlations were seen between MQI and MetS, FBS, WC, HDL-C, and BP. Moreover, in the adjusted model, the GDQS was negatively and significantly associated with the risk of low HDL-C. No significant association was observed between GDQS and MetS, FBS, WC, TG, and BP.Conclusion: The GDQS and MQI were not correlated with the risk of MetS. A higher diet quality measured by GDQS and MQI can be inversely associated with the risk of dyslipidemia as a major component of MetS.